Hiperactividad y su incidencia en el aprendizaje de los niños del subnivel 2 de educación inicial en la Escuela “Babahoyo” - Garcia Mina, Janeth Elizabeth (2019)
This research that is addressed to children and children with hyperactivity of the Babahoyo school during this process proved that there is little attention and idifference in teachers because they do not know about the (subject), and there is no communication relationship of the clinical psychologist with teachers and in turn when enrolling the child in the institution the parents have no knowledge that their child has hyperactivity they think they are restless or spoiled. This project is important because it will help teachers parents to have an assertive communication in family and learn to observe since the child is born and his childhood about the different, different disorders or disabilities that can occur during childhood. It can be improved with talks to teachers so that parents can integrate into this problem, so that they are active participants and help and thus have a better coexistence with the boy or girl who have these hyperactivity disorders the same as they have as incidence: lack of concentration, behavior and difficulty staying seated in one place. To conclude, it is important to highlight the research that has been done in order to highlight these special cases that occur especially in educational institutions, hoping that these contributions are very useful for the educational community of this campus and can be of contribution to others. institutions that present these same cases of hyperactivity